Muscle activation patterns and muscle synergies reflect different modes of coordination during upper extremity movement - Chen, Xiaoling; Dong, Xiaojiao; Feng, Yange; Jiao, Yuntao; Yu, Jian; Song, Yan; Li, Xinxin; Zhang, Lijie; Hou, Peiguo; Xie, Ping (Frontiers in Human Neuroscience, 2023)
A core issue in motor control is how the central nervous system generates and selects the muscle activation patterns necessary to achieve a variety of behaviors and movements. Extensive researches have verified that it is the foundation to induce a complex movement by the modular combinations of several muscles with synergetic relationship. However, a few studies focus on the synergetic similarity and dissimilarity among different types of movements, especially for the upper extremity movements. In this study, we introduced the non-negative matrix factorization (NMF) method to explore the muscle activation patterns and synergy structure under 6 types of movements, involving the hand open (HO), hand close (HC), wrist flexion (WF), wrist extension (WE), supination (SU) and pronation (PR). For this, we enrolled 10 healthy subjects to record the electromyography signal for NMF calculation. The results showed a highly modular similarity of the muscle synergy among subjects under the same movement. Further spearman analysis indicated significant similarities among HO-WE, HO-SU, and WE-SU (p<0.001). Additionally, we also found the shared synergy and special synergy in activation patterns among different movements. This study confirmed the theory of modular structure in the central nervous system, which yields a stable synergetic pattern under the same movement. Our findings on muscle synergy will be of great significance to motor control and even to the clinical assessment techniques.